As tecnologias Digitais de Informação e Comunicação e as metodologias ativas na prática docente : reflexões sobre o uso da plataforma Google Workspace for Education - Marcondes, Rosana Maria Santos Torres (2021)
This dissertation is based on a research focused on the use of the educational platform: Google Workspace for Education which was guided by the question: how do teachers manage the Google Workspace for Education platform in their teaching practices during emergency remote teaching? Aiming at answers to the questioning, the investigation was developed according to the assumptions of qualitative research and descriptive study. It aims to comprehend G Suite for Education platform use in emergency remote teaching as a didactic pedagogical resource in the development of teaching practices in 8th year of elementary school at a private school in Aracaju, SE. The instruments adopted for data production were the classroom observation in the virtual environment and semi-structured online interview through videoconference. The analysis of the collected data was carried out from the perspective of Laurence Bardin's content analysis technique. As a result, we understand that teachers used the Google Workspace for Education platform to ensure the continuity of the school year, as the applications enabled teaching work in emergency remote teaching. The research also showed that the teachers overcame difficulties presented by the context and also the fact that teaching is remote and allows the use of different technological resources did not make it more dynamic than in-person, hence the effectiveness of a face-to-face or virtual class regardless of the technology used. Thus, we realize teachers although they have widely used technology in their classes from their practices and according to the appropriation stages, are at different levels of appropriation: exposure, adoption, adaptation and appropriation. We also did not identify actions that would lead to the innovation stage of teaching practice. We also found that they have faced this moment of emergency remote education with responsibility, seeking to overcome obstacles and showing a predisposition for continuing education. Finally, we conclude that each teacher gave their best within their possibilities, which was possible to accomplish at a time of great social, educational and personal challenges.